‘Like the stranger at a funeral who cries more than the bereaved’: ethical dilemmas in ethnographic research with children - Okyere, Samuel (SAGE, 2017)
This article contributes to debates on the practicality and utility of prior ethical review in ethnography and qualitative research using an ethnography of children’s involvement in artisanal gold mining work in Ghana as a case study. Reflecting on dilemmas and obstacles encountered in attempts to employ prescribed institutional ethical guidance modelled for childhood research in the UK during the fieldwork, the discussion brings to attention some of the problems that can arise when ethical guidance is not anchored in the lived realities or value systems of the setting in which fieldwork is conducted. The article seeks to rejuvenate calls for more flexible and socio-culturally responsive ethical review and practice as an alternative to the prescriptive ethical regimes.